Probabilidade de ocorrência de temperaturas máximas e mínimas mensais prejudiciais e favoráveis aos cultivos agrícolas em Minas Gerais, Bahia e Rio Grande do Sul - Borges, Rodrigo de Morais (2020)
In the face of speculation about climate change, global warming, impact on the environment and agriculture, the study of the probability of the occurrence of harmful and environment-friendly maximum and minimum air temperatures becomes extremely important and relevant to subsidize and assist farmers and farmers. agribusiness sectors, mainly when it comes to agricultural planning. Thus, the present study aimed to determine the probability of 90% of the occurrence of harmful maximum and minimum monthly air temperatures favorable to different agricultural crops in the states of Minas Gerais, Bahia and Rio Grande do Sul. A historical series was used, of maximum and minimum monthly air temperatures from 1961 to 2019, 58 years of temperature data obtained from the database of the National Meteorological Institute (INMET) of the states of Minas Gerais, Bahia and Rio Grande do Sul. The Kolmogorov-Smirnov tests was used to verify the adherence of the data to the normal, lognormal, gamma and Weibull distributions. The probability distribution that had the best adherence to the data set was the Normal distribution and it was used to calculate the 90% probability of occurring harmful and favorable monthly maximum and minimum air temperatures for agricultural crops in the states studied. Maps were drawn up with isolines with a probability of 90% of maximum and minimum monthly temperatures occurring during the 12 months of the year. The maps were generated via the geographic information system (GIS) with software “QGIS 3.12.3”. Data were analyzed using Office Excel® spreadsheets and R software. After data treatment, based on the mean and standard deviation, the probability of 90% of temperatures equal or higher for maximum temperature and equal or less for minimum temperatures were calculated. The probability values for each meteorological station were interpolated, using the IDW method, and later the 90% probability isolines were created for the 12 months of the year. With the elaboration of the maps, they show the importance of the probabilistic study of the occurrence of certain temperatures, because in all the states' territory it is possible to have a visualization of the 90% probability of occurrence of a certain temperature that can be harmful or favorable for the development of a culture on occasion, throughout the 12 months of the year. Being an effective way that can contribute substantially to agricultural planning, so that phenological stages coincide in times when the temperature can exert on them in the best possible way, without harming them or in certain situations, favoring them.